Process evaluation of enhanced community health system activities to improve detection and management of acute malnutrition in Samburu County, Kenya - Tammary Esho; Monica Nthamba Ng'ang'a (PLOS Glob Public Health, 2026)
Acute malnutrition remains a persistent public health concern in Kenya's arid and semi-arid lands, including Samburu County, where the prevalence of global acute malnutrition (GAM) frequently exceeds the emergency threshold of 15%. Since 2023, a program collaborating with the county government has been implementing a range of enhanced community health systems activities focused on improving early detection and management of acute malnutrition. This process evaluation of the program used qualitative research methods and was guided by the Medical Research Council process evaluation framework. Twenty-five key informant interviews were conducted with program implementers, including 10 community health assistants (CHAs), 10 community health promoters (CHPs), and 5 Samburu County staff. The data were analyzed thematically using Nvivo software. Participants described how training and mentoring on integrated management of acute malnutrition (IMAM) and commodity management improved CHPs' and CHAs' knowledge and confidence in acute malnutrition case identification, treatment, and follow-up. Reprinting of paper IMAM registers enhanced monitoring and follow-up of cases, but CHPs had challenges using the new electronic health information system. Most CHAs and Samburu County staff described how the savings and loan associations supported by the project boosted CHPs' and CHAs' economic resilience and reinforced their commitment and motivation to do their work. Despite these gains, participants identified persistent barriers to implementation, including logistical and transport challenges, commodity stockouts, limited communications infrastructure, and continued gaps in training and human resources. Misuse of commodities for GAM treatment and community pressure on CHPs, also constrained program implementation. In conclusion, the project should work with the county government to develop strategies to address these challenges and further strengthen program implementation.
Keywords: community health system; Community Health System; Acute Malnutrition; Samburu County